The Influence of Work Motivation and Leadership on Employee Performance at UPT Balai Yasa Yogyakarta - Nathasya Herlita; Teguh Iman Santoso (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee performance is a crucial factor that influences the success of an organization, including at UPT Balai Yasa Yogyakarta, which operates in the field of railway maintenance. In efforts to improve performance, two crucial factors to consider are work motivation and leadership. Work motivation encourages employees to perform more optimally, while effective leadership provides direction, support, and a conducive work environment. However, the suboptimal performance of some employees indicates the need to evaluate the role of these two factors. This research seeks to empirically investigate the impact of work motivation and leadership on the performance of employees at UPT Balai Yasa Yogyakarta. This study employs a quantitative method with a descriptive approach to objectively and systematically examine the relationships among variables, using data gathered through questionnaires distributed to 196 employees at UPT Balai Yasa Yogyakarta. The data utilized in this study includes both primary and secondary sources, which are analyzed through descriptive analysis and SEM-PLS. The results show that both work motivation and leadership positively influence employee performance. High levels of motivation, coupled with effective leadership, contribute to improved overall performance. The impact of work motivation on employee performance is similar for both male and female employees, indicating no significant differences between the two groups. Conversely, there is a gender-based difference in the impact of leadership, highlighting the need for a more flexible and adaptive leadership approach to effectively engage and motivate all employees.